Implementation of Merdeka Curriculum in Islamic Science at the Private Madrasah Tsanawiyah Nur Ibrahimy Rantauprapat - Hutabarat, Fazri; Syawaluddin, Fauzi Ahmad; Siregar, Jailani Syahputra (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This research aims to determine the Merdeka Curriculum implementation in agama Islam subject (PAI) in Madrasah Tsanawiyah (MTS) Nur Ibrahimy Labuhanbatu. The subject of this research is a teacher who taught agama Islam subject in the first to third grade in Mafrasah Tsanawiyah Nur Ibrahimy. The study was conducted through qualitative analysis with observation, questionnaire, and structured interviews as research instruments. The result shows that the Merdeka Curriculum has not been implemented optimally in PAI learning at Madrasah Tsanawiyah Swasta Nur Ibrahimy. The two main obstacles to implementing this curriculum are the lack of implementation of P5 and teacher-centered learning. Meanwhile, the most significant challenges come from limited resources and infrastructure, the readiness of teaching and education staff, and obstacles in implementing P5. To overcome this, schools are required to be proactive in supporting the implementation of the Merdeka Curriculum through training. Keywords: Education, Merdeka Curriculum, MTS, PAI